Detection of Antibody to Envelope (E2) Antigen of Hepatitis C Virus - RK Chaudhary; E Burres (Canadian Journal of Infectious Diseases)
One hundred and four clinical specimens from provincial public health laboratories were tested for antibody to hepatitis C virus (HCV) envelope protein (anti-E2). To evaluate the effect of hypervariability of E2 region on anti-E2 assay, 49 recombinant immunoblot assay (RIBA) 3.0 positive samples were genotyped. All 49 genotyped samples were positive for anti-E2. Eight of 12 (67%) indeterminate, HCV RNA positive samples were anti-E2 reactive. Nine of 30 (30%) indeterminate, HCV RNA negative samples were also positive for anti-E2. Anti-E2 was detected in two of 13 (15%) RIBA-negative and enzyme immunoassays-positive samples. Although small number of samples were tested, the results showed that it may be possible to resolve indeterminate samples with the anti-E2 assay.